Chemical and physical attributes of two substratum for eucalypt seedling production - Wadas Lopes, Jane Luisa [UNESP]; Guerrini, Iraê Amaral [UNESP]; Cury Saad, Joao Carlos [UNESP]; Silva, Magali Ribeiro da [UNESP] (Universidade Federal de Lavras (UFLA), 2008)
This work evaluated the viability of one commercial substrate with pinus bark, vermiculite and 30% of coconut fiber for Eucalyptus grandis seedlings production under different water management: 6, 8, 10, 12 e 14 mm day(-1). In relation to the substrates, it was evaluated, before and after the seedlings production, the total content of carbon, nitrogen and organic substances, pH and EC of the extract, the content of macronutrients (P, K, Ca, S, Mg) and macronutrients (B, Fe, Mn, Cu, Zn), as well as total porosity, density and water retention. It was evaluated the macro and mcronutrients accumulation in the roots and in the aerial part of the seedlings, 105 days after sowing. It was concluded that the substrates presented some distinct properties of those cited as ideal for production in containers with irrigation and fertilization. At the end of the production process, both substrates registered nutrient content little influenced by water management what would guarantee the initial development of the plants in the field.
Keywords: Eucalyptus grandis; nursery; irrigation